2023
DOI: 10.3389/fimmu.2023.1111569
|View full text |Cite
|
Sign up to set email alerts
|

Role of mTOR inhibitor in the cellular and humoral immune response to a booster dose of SARS-CoV-2 mRNA-1273 vaccine in kidney transplant recipients

Abstract: BackgroundImmunocompromised patients have an increased risk of developing severe COVID disease, as well as a tendency to suboptimal responses to vaccines. The objective of this study was to evaluate the specific cellular and humoral adaptive immune responses of a cohort of kidney transplant recipients (KTR) after 3 doses of mRNA-1273 vaccine and to determinate the main factors involved.MethodsProspective observational study in 221 KTR (149 non infected), 55 healthy volunteers (HV) and 23 dialysis patients (DP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In immunocompetent individuals, low IgG levels after SARS-CoV-2 vaccination were associated with a low frequency of specific CD8+ T-cell memory and failed to control the delta and omicron variants of COVID-19 ( 34 ). This is in line with recent studies that showed IFNγ–producing CD8-T cells correlate with IgG titer and neutralization ( 68 ). In this study, anti-SARS-CoV-2 IgG levels were not correlated with CD8 CM/TM T cells.…”
Section: Discussionsupporting
confidence: 92%
“…In immunocompetent individuals, low IgG levels after SARS-CoV-2 vaccination were associated with a low frequency of specific CD8+ T-cell memory and failed to control the delta and omicron variants of COVID-19 ( 34 ). This is in line with recent studies that showed IFNγ–producing CD8-T cells correlate with IgG titer and neutralization ( 68 ). In this study, anti-SARS-CoV-2 IgG levels were not correlated with CD8 CM/TM T cells.…”
Section: Discussionsupporting
confidence: 92%
“…A study of liver and heart transplant recipients found no evidence indicating that CNIs or other immunosuppressive medications were associated with a diminished cellular response [ 39 ]. A study with a small number of KTRs similarly showed no association between CNI and diminished cellular response [ 40 ]. However, a recent meta-analysis showed tacrolimus (vs. a non-tacrolimus regimen) was associated with lower odds of positive cellular immune response (pooled OR 0.5) in KTRs [ 18 ].…”
Section: Immunosuppression and Vaccine Response In Solid Organ Transp...mentioning
confidence: 99%